154k views
0 votes
Solve for ef=epd, for e

1 Answer

2 votes

To do this, divide by pd into both sides of the equation:


\begin{gathered} f=\text{epd} \\ (f)/(pd)=\frac{\text{epd}}{pd} \end{gathered}

When dividing by pd into both sides of the equation, you can see that on the right side this term can be canceled both in the numerator and in the denominator, therefore, on the right side only the variable of interest remains, e


(f)/(pd)=e

Therefore, the solution for e is


e=(f)/(pd)

User Balamurugan
by
4.8k points